A THE EFFECTIVENESS OF SERVICE ABILITY FOR INTERNSHIP STUDENTS USING THE LEARNING BY DOING METHOD KAI KERTAPATI STATION - Aditya Andriansyah; Fera Indasari (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2022)
Effective training in the world of work, definitely requires the right method in improving the basic skills of employees. The appropriate method in building one's potential and competence by providing real experience is the learning by doing method. Learning by doing is an attempt to increase experience and knowledge through a learning process that combines learning while practicing, by prioritizing action rather than theory. The type of research used by the author is a qualitative descriptive approach, a method used to analyze research results, but is not used. to create more mature conclusions. The sources of data obtained in the research carried out are 1. Primary data sources include basic data obtained directly from the research object. 2. Secondary data sources include literature review of research journals. The learning by doing method directly develops affective, cognitive and emotional abilities. By increasing these competencies, students can maximize internships in carrying out their duties, and can become a benchmark or standardization in order to be able to compete in this increasingly wide world of work. Based on the results of the interview, the researcher can conclude that the training provided by the customer case sub unit, Pak Ahmad, in increasing the effectiveness of student internship services, has been quite effective in growing self-confidence and developing the competencies needed to compete in the world of work, although there is a sample of respondents lacking agree with the given method, but overall the interns accept it effectively.